2012
DOI: 10.1371/journal.pone.0046932
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination against Rural-to-Urban Migrants: The Role of the Hukou System in China

Abstract: China's rural-urban dual society system is instituted by its unique hukou system. This system causes inequalities in social status between permanent urban and rural residents, and discrimination against rural-to-urban migrants is thus prevalent. A series of studies, based on system justification theory, sought to address the impact of the hukou system on the discrimination against rural-to-urban migrants. Study 1 showed that the justification of the hukou system could predict discrimination operationalized usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 41 publications
0
82
1
Order By: Relevance
“…Many female migrants experience challenges finding skilled or formal employment (Kuang & Liu, 2012), and, thus, frequently seek jobs in entertainment venues, such as bars, nightclubs, and karaoke parlors, which are common in urban settings throughout China. Patrons (mostly male) who visit these venues generally pay fees in exchange for companionship with a female employee, with whom they engage in various social activities, such as singing karaoke, gambling, and drinking (Huang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many female migrants experience challenges finding skilled or formal employment (Kuang & Liu, 2012), and, thus, frequently seek jobs in entertainment venues, such as bars, nightclubs, and karaoke parlors, which are common in urban settings throughout China. Patrons (mostly male) who visit these venues generally pay fees in exchange for companionship with a female employee, with whom they engage in various social activities, such as singing karaoke, gambling, and drinking (Huang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Participants were asked to read an article (Kuang and Liu, 2012, see in Appendix) ostensibly excerpted from newspapers. The article in the legitimate condition explained that the Hukou system, which categorizes Chinese citizens as either urban or rural, was legitimate and would not be abolished in the future (see Appendix 3).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, when the social hierarchy is perceived as illegitimate, advantaged group members may feel shameful and guilty about their exhibition of ingroup favoritism on status-relevant dimensions, so they are likely to exhibit more positive outgroup evaluation and egalitarianism (Shepherd et al, 2013a,b) to make them feel better. Some research (Kuang and Liu, 2012) has revealed that advantaged group members showed less discrimination to disadvantaged group members when they were told that the social hierarchy status quo was illegitimate (versus legitimate).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, tens of millions of migrant workers' children are left in rural hometowns because they struggle to access education in the cities (Branigan, 2014). The unfair treatment that migrant workers suffer in cities due to their lack of urban household registration also leads to social stigma and feelings of being marginalised (Kuang & Liu, 2012). The interviews revealed that migrant workers' passive physiological feelings made them less confident about joining the urban old-age pension scheme.…”
Section: Social Stigma Resulting From the Dual-citizenship Systemmentioning
confidence: 99%